IMPORTANCE OF SUSTAINABLE TOURISM DEVELOPMENT IN TERMS OF ECONOMIC DEVELOPMENT - BRANKICA TODOROVIC (Analele Universităţii Constantin Brâncuşi din Târgu Jiu : Seria Economie, 2015)
The quality of tourist resources and tourist products, competitive ability and positioning of the destinations in the tourist market affect the economic development of the national economy. Natural resources are key, but under-utilized resources necessary for the tourism development, whereby reaching the level where the key development resources are on the verge of carrying capacities, thus making the model structure of the future development to be a significant contribution in searching the optimal model of sustainable development. The paper points to the importance of previous positive experience in the development of tourism and related activities especially in terms of development planning in accordance with the available resources, spatial opportunities and sustainable development. The research the possibility of defining an optimal model for sustainable tourism development in the case of mountain destinations in Zlatibor District will indicate the need to precisely define economic-geographical resources which determine the individual role of an each resource in creating the tourist offer, as well as, to show that the inadequate management of tourist resources and marketing activities leads to their degradation.